The myotonic dystrophies: diagnosis and management - C Turner; David Hilton‐Jones (2010)
There are currently two clinically and molecularly defined forms of myotonic dystrophy: (1) myotonic dystrophy type 1 (DM1), also known as ‘Steinert’s disease9; and (2) myotonic dystrophy type 2 (DM2), also known as proximal myotonic myopathy. DM1 and DM2 are progressive multisystem genetic disorders with several clinical and genetic features in common. DM1 is the most common form of adult onset muscular dystrophy whereas DM2 tends to have a milder phenotype with later onset of symptoms and is rarer than DM1. This review will focus on the clinical features, diagnosis and management of DM1 and DM2 and will briefly discuss the recent advances in the understanding of the molecular pathogenesis of these diseases with particular reference to new treatments using gene therapy.